The family "Thelypteridaceae" in Europe - Holtumm, R.E. (Universidad de Málaga, Servicio de Publicaciones, 1983)
Thelypteridaceae are mainly tropical ferns, the total number of species is about one thousand. The five European species represent five different groups, each of which has recently been accorded generic status. Thelypteris palustris Schott (including three varieties) extends throughout north temperate regions, with a closely allied species south of the equator; chromosome number n=35. Phaegopteris connectilis (Michx) Watt (triploid with base number 30) and Oreopteris limbosperma (All.) Holub (n=34) are members of small genera confined to north temperate regions. Stegnogramma pozoi (Lag.) K. Iwats. (n=36) represents a genus of 12-15 species, mainly in Africa and Asia, with one in Mexico. Christella dentata (Forsk.) Brownsey & Jermy is a wide-ranging and variable tetraploid species of a pantropic genus (c. 60 spp) the centre of distribution of wich appears to be Burma-Assam (base number 36).The genus Cyclosurus (s. str.) comprises a small pantropic group of species with grow (like Thelypteris) in open permanently swampy ground; I belive Cyclosorus and Thelypteris to be closely related genera. Stegnogramma is related to Sphaerostephanos which (in arrangement of Holttum) is the most diversified genus in the Old World with c. 140 spp. in Malesia . Christella is probably also related to Sphaerostephanos though less nearly than Stegnogramma.

Las Thelypteridaceae son helechos principalmente tropicales, comprende aproximadamente mil especies. Las cinco especies europeas representan cinco grupos diferentes cada uno de los cuales ha recibido recientemente un estatus genérico. Thelypteris palustris Schott (incluyendo tres variedades) se extiende por las regiones templadas del norte, con un conjunto de especies próximas al sur del ecuador; el número cromosómico es n=35. Phegopteris connectilis (Michx) Watt (triploide con número básico 30) y Oreopteris limbosperma (All.) Holub (n=34), son miembros de pequeños géneros confinados a las regiones templadas del norte.Stegnogramma pozoi (Lag.) K. Iwats. (n=36) representa un género de 12-15 especies principalmente de Africa y Asia con una en Méjico. Christe lla dentata (Forsk.) Brownsey & Jermy es una variable especie tetraploide de amplia distribución cuyo género pantropical (cerca de 60 especies) parece tener su centro de distribución en Burma-Assam (número básico 36).El género Cyclosorus (s. str.) comprende un pequeño grupo de especies pantropicales que viven en llanuras permanentemente pantanosas. Creemos que Cyclosorus y Thelypteris son géneros muy emparentados. Stegnogramma está relacionado con Sphaerostephanos, el cual (en la ordenación de Holttum) es el género más diversificado en el viejo mundo con cerca de 140 especies en Malasia Christella esta tambien relacionada,probablemente, con Sphaerostephanos aunque su proximidad es menor que la mantenida con Stegnogramma.